Teachers Questioning Techniques for Classroom Interaction In English Speaking Class - Erna Irmayanti (Journal of English Education Program (JEEP), 2019)
English is a main subject in Chinese English classes, which requires plenty of practice, needs cooperation between theteacher and students in class to jointly fulfill the verbal communication and the teaching-learning procedure. Classroom questioning, the skill of the elicitation method of teaching that is student-oriented and advocated today, gives an incentive to communicative activities in English. Raising questions effectively is a major method of the teacher who guides his students to think actively, fostering students’ ability of analysis and creation. It is also an essential way for the teacher to output information and obtain feedback, and an important channel to exchange ideas between the teacher and students. Therefore, the teacher must pay great attention to the skill of asking questions in English class. Each question must be presented to accomplish the teaching objective and task. Only in this way may the English teachers ask question effectively and improve the skill of questioning so as to make contribution to our Chinese English education. To begin with some elemental definitions, this paper discusses some basic knowledge of questions, and then explores the skill of questioning in English class about the preparing, designing, controlling and evaluating of questioning. Finally the benefit of the skill is studied with abundant teaching cases. The paper analyzes tentative in English class by integrating theory with practice. Thus, the skills of questioning are further understood in English classes.Keywords: English teaching, Questioning, Skills, Interaction teaching.